The Decrees of Necessity and Urgency in relation to the Presidential Power to Dictate Extraordinary Measures contained in section 20 of article 211 of the Constitution - Eguiguren Praeli, Francisco José (1986)
This paper analyzes the decrees of necessity and urgency as a mechanism introduced in the Peruvian Constitution of 1979 that allows the president to implement extraordinary measures in economic and financial matters in those situations where the national interest is affected. This power is recognized in Article 211, paragraph 20 of the Constitution and it is stated that it seeks to strengthen the power of the Executive, giving it more powers in the legislative area to respond quickly in critical cases. However, it is also pointed out that the constitutional norm is imprecise as to the hierarchy of these decrees, since it does not specify whether they have the force of law, which leads to varied interpretations and to questioning their control by Congress. Therefore, the author argues that it is necessary to establish a legal category for these decrees; that the exceptional nature inherent to these extraordinary measures requires their rational and restricted use to situations of effective necessity and urgency; and, finally, that these measures have the vocation and force of law, so that it is up to Congress to review and validate these decrees in order to avoid abuses and ensure respect for the ordinary legislative processes.